Pengaruh Lama Penyimpanan Kantong Darah terhadap Kadar Hemoglobin pada Komponen Whole Blood di Unit Donor Darah PMI Kota Palangka Raya - Windya Nazmatur Rahmah; Adinda Chairunnissa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Hemoglobin levels are used as a requisite for determining blood transfusion therapy for patients with anemia. Prior to blood transfusion, it is initially stored in blood bags that contain CPDA-1 anticoagulant with a shelf life for 35 days at temperature 2-6°C with a FIFO system. The purpose of this study was to determine hemoglobin levels in blood bags on the third dan fifth day of increasing the patient’s hemoglobin level in Unit Donor Darah PMI Palangkaraya. The research was conducted with a descriptive method with a Linear Regression research design. The sample used is a whole blood bag of blood obtained by purposive sampling technique with a total sample is 30 blood bags. The paired Linear Regression on the while the whole blood bags obtained p < 0.05 indicating that there was effet storage in hemoglobin levels on the third day, and p > 0.05 indicating that was no effect storage in hemoglobin levels on the fifth day.